Web-oriented software system for mutual student learning - Illiashenko, I. (ХНУРЕ, 2023)
In today's realities, schoolchildren, students, teachers and even people who are not currently involved in learning need a knowledge exchange system that will help them not spend money on commercial courses. This system should have a clear structure, an intuitive and convenient interface, contain all the necessary functionality related to the direct purpose of such a platform. A platform for online mutual learning is what any modern person who wants to develop and spread their knowledge with society on mutually beneficial terms needs - knowledge in exchange for knowledge